Reflection of overload and manufactured supplements on the health of the bodybuilder A field study in some sports halls for bodybuilding in the state of Sétif- Algeria- - madaci, lotfi; Louati , abd esselam (sports creativity, 2023)
The Aim of This Stydy Is to identify the extent affect of overload and manufactured nutritional supplements on the health of the bodybuilder athletes. The researchers used the descriptive approach with a groupe of people consisting of 40 athletes who were selected at random, and they conducted a questionnaire to collect data, to be treated statistically. By the end their results show That : Overload has a negative effects on the health of the bodybuilding athletes. Moreover, the manufactured supplements has an impact on the health of the bodybuilding athletes. The researchers recommended the need of qualified trainers in the field of bodybuilding in the sports halls.